The Relationship between Self Efficacy and Academic Workloads with Stress of Nursing Internship: Literature Review - Mitha Permata Dini; Rizki Fitryasari; Candra Panji Asmoro (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2020)
Introduction: Stress in students who undergo clinical practice is still a serious problem because it can have an impact on health and academic achievement. Self-efficacy and academic workload can affect the stress of nursing students. This study aims to identify the relationship between self-efficacy and academic workload and stress of nursing internship.Method: The research method used literature review design. Search journals or articles using a database indexed Scopus, ScienceDirect, Google Scholar. Variables that used to search the articles (self efficacy, academic workload, and stress). The framework used to review is PICOS and the inclusion criteria used are English and Indonesian journals with issues from 2015 to 2020. The results of the search for articles before the examination were carried out, there were 385 studies, furthermore, 10 studies that matched the inclusion criteria were reviewed. Narrative analysis and data tabulation of articles or journals is carried out.Results: The results of this study indicate that self-efficacy helps students increase competence so that students can complete assignments and take practical steps in challenging situations so that this can reduce stressors and reduce stress. In addition, stress is also influenced by academic workload, excessive workload can trigger stress. Academic stress that occurs has a negative impact on student competence and academic performance.Conclusion: Self-efficacy helps students reduce stress experienced during clinical practice. Academic workload is the biggest stressor for nursing students who undergo clinical practice.